Urgensi Integritas Nasional Sebagai Salah Satu Parameter Persatuan dan Kesatuan Bangsa - Jumadilla Afifah; Nelfa Tri Safitri; Bambang Trisno (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2024)
Indonesia, an archipelago with rich culture and diverse ethnic groups, is faced with the challenge of maintaining national unity. National integrity, defined as a state in which all people have a sense of unity and love for the country, is an important parameter to achieve this goal. This paper discusses the urgency of national integration as one of the parameters of national unity. First, national integration can strengthen the sense of unity by fostering a sense of patriotism and nationalism among the people. Second, national integration can increase national stability by reducing the potential for conflict and division between community groups. Third, national integration can spur national development by creating a conducive and safe atmosphere for the implementation of development. Fourth, national integration can increase the nation's competitiveness by creating a society that is united and has a common goal to achieve national progress. Fifth, national integration can maintain territorial integrity by preventing the disintegration of the nation that can result in the division of the country.